O funcionamento do sistema de freios e contrapesos no âmbito do poder judiciário - Santos, Adriana Cecilio Marco dos (2021)
The study of the system of checks and balances is essential for Constitutional Law. The research begins by tracing the historical context of the separation of Powers and the system of checks and balances. In the next chapter, concepts that define the tripartition of the Powers and the system of checks and balances are presented, proposing a classification that divides the mechanisms into: “brakes”, ordering their modalities in internal and external; and “counterweights”, dividing them into positive and negative; the active and passive status of the Powers when categorizing the mechanisms of the checks and balances system is categorized; and the typical and atypical functions of each of the Powers are specified. The investigation continues first by presenting the mechanisms available to the Executive and Legislative Powers. This examination proves to be necessary in order to draw a panorama of the constitutional engineering present in the Brazilian Constitution of 1988. Continuous act, it starts to deal with the Judiciary Power. The proposed classification allows for individual analysis within each of the Powers. In this block, the verification of the instruments present in the Judiciary Power shows the lack of external brakes and effective negative balances, as well as the internal attempt to overcome the only positive balance present in the Brazilian constitutional architecture reveals a concentration of power harmful to the separation of the Powers, considering the historical lesson that warns about the possibility of degeneration, when there are no mechanisms capable of preventing abuse. Or I follow work or descriptive method, making use of historical, doctrinal and documentary research, in addition to the line of research “Justice, Company and Sustainability”.